SMARTPHONE ROLES IN TRIGGERING STUDENTS’ READING SKILL - Griffin Mewoh; Andi Hamzah Fansury; Maulina Maulina; Ramli Ramli (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The role of smartphone in the field of education has become a major support for teachers and students in learning and teaching areas. Teachers and students have been helped a lot to access any sources to collect many information as much as they want through this technology. Smartphone provides many contents that can be read everywhere not only in the classroom such as journal, articles, e-books and any others. As a recent technology, smartphone offers valuable opportunities for teachers to create an effective strategy in teaching especially to attract students’ interest to read via smartphone. In this literature review, I would like to find and share the role of smartphone in triggering students reading skill. And the methodology that I would like to use is the qualitative method in which there will be some interviews in collecting the data. And reading through all the result of the interviews and drawing some connection between smartphone and reading skill to analyze the data, the participants are from VIII grade students of Makassar Adventist Junior High School. As a result, those students who are reading through digital text (smartphone) have unlimited access of information to enhance their reading skills than those who are not. Here the writer found out that smartphone plays a role in triggering students’ reading skill.